Investigating the Impact of Work–Family Balance on Job Engagement: A Systematic Review - Al- Enazi, Hessa Eid N A (Journal of Ecohumanism, 2025)
In contemporary organizational research, work–family balance and job engagement have emerged as two interrelated constructs critical to employee well-being and organizational effectiveness. This study conducts a systematic review of 25 empirical and conceptual studies to examine the extent to which work–family balance affects job engagement, with a particular emphasis on employees at Qatar University. The review was conducted in line with PRISMA guidelines, ensuring methodological rigor and transparency. The findings indicate that work–family balance is strongly associated with higher levels of employee engagement, creativity, and performance, while imbalances are linked to stress, reduced productivity, and negative spillover into personal lives. Evidence from Arab and international contexts highlights both universal patterns and context-specific dynamics, especially in higher education institutions. By synthesizing theoretical and empirical insights, this review contributes to a better understanding of the drivers of engagement and provides practical implications for university leaders in creating a supportive and balanced work environment. The study also identifies gaps in the literature and proposes recommendations for future research on organizational strategies that promote sustainable work–life integration in academia.